Openings Effect on the Performance of Reinforced Concrete Beams Loaded in Bending and Shear - El Ame, F.; Mwero, J. N.; Kabubo, C. K. (Engineering, Technology & Applied Science Research, 2020)
Transverse openings are often provided to reinforced concrete beams to accommodate utility ducts and pipes. This technique is usually adopted to avoid the creation of dead space in structures caused by extended dropped ceilings and leads to significant cost saving. On the other hand, the provision of openings through a beam creates a reduction in its strength and affects serviceability. In this study, ten reinforced concrete beams were cast using C30 concrete. Material characterization and engineering properties tests were carried out to ensure compliance with the requirements provided by the codes of practice. The effect of vertical positioning and size of openings was investigated through subjecting the beams to a four-point bending test after 28 days of curing. Maximum load capacity, first cracking load, and deflections at mid-span were recorded and crack pattern and failure mode were evaluated. Test data showed that openings of depth greater than 0.4d significantly affect the beams’ strength and lead to earlier cracking, while the failure mode remains essentially the same, a diagonal tension crack through the opening except for opening of 0.5d size where the failure occurred by a sudden formation of two independent shear cracks above and below the opening. When holes were located above the centroid of the section, the beams exhibited a lesser deflection characterized by the absence of plastic deformation. Furthermore, a significant reduction in strength was recorded compared to cases where the positioning of openings was in tension chords. This was validated using equations from the ACI code of reinforced concrete design.